Gap analysis - potatoes occurrences - Castañeda Álvarez, Nora P. (2015)
Records (with and without coordinates) representing germplasm accessions and sightings of the wild relatives of potato. These records were used as input to assess the ex situ conservation urgency of 73 wild relatives of potato